Pemanfaatan Sms Gateway Dalam Mendukung Proses Pelayanan Pelanggan Pada Gaudi Clothing - Jiwany, Larasathi; Nurseptiani, Alya; Maulindah, Rafika; Situmorang, Ruth Christin Aprilia; Rahmadini, Vira Putri; Ibrahim, Ali (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2019)
Many large companies today do not pay attention to customer service relationships. Companies that often consider products sold are superior products that are sought after by the public. While good service will make customers loyal to the company. Imagine the amount of loss received if you do not pay attention to customer service. One way to overcome this problem is by using technology and marketing concepts CRM (Customer Relationship Management). Application (Short Message Service) SMS Gateway as a technology used to support effective and efficient CRM concepts. At present, all customers have mobile phones, so SMS is chosen as a good facility to deliver information because it is fast and reaches directly to customers, besides because of its low cost. The purpose of this study is to study the implementation of SMS Gateways that facilitate companies in conveying information to Gaudi Clothing customers. With the SMS Gateway, companies can broadcast attractive promos and new products to customers. It is expected to reduce promotions through brochures due to printing costs and waste. In designing this system, the data collection methods used are literature studies, interviews, observations and questionnaires. Application of SMS Gateway with the help of Nexmo application. Based on the research conducted, the percentage value obtained was 70.75% which was proposed by the AGREE criteria. Gaudi Entrance Clothing. So using the SMS Gateway to support the customer service process on Gaudi Clothing, can be a good solution because it is useful to support the service process and relationships with customers of Gaudi Clothing